The Leverage as A Mediating Variable on Tax Avoidance - Juli Ratnawati; Dwi Cahyo Utomo (Politeknik Caltex Riau, 2022)
ABSTRACT The purpose of the study was to determine the effect of executive compensation, executive character, sales growth, and capital intensity on tax avoidance with leverage as a mediating variable. This study uses samples from manufacturing companies in the various industrial sector listed on the Indonesia Stock Exchange (IDX) during the 2017-2020 period. This study uses a purposive sampling method and the total sample are 48 companies. The data analytical technique is multiple linear regression analysis. The test results reveal that executive compensation, executive compensation, sales growth, capital intensity have no effect on tax avoidance. While, the executive character has an effect on tax avoidance. Leverage can mediate the effect of capital intensity on tax avoidance. Leverage can not mediate the effect of executive compensation, executive character, and sales growth on tax avoidance. Keywords: Executive Compensation, Executive Character, Sales Growth, Capital Intensity, Tax Avoidance, Leverage.